PERLINDUNGAN DATA PRIBADI SEBAGAI BAGIAN DARI HAK ASASI MANUSIA ATAS PERLINDUNGAN DIRI PRIBADI Suatu Tinjauan Komparatif Dengan Peraturan Perundang-Undangan Di Negara Lain - Hanifan Niffari (Program Magister Ilmu Hukum Universitas Pancasila, 2020)
Data privacy protection as a part of personal privacy protection stated in Article 28Gparagraph 1 The 1945 Constitution of Republic Indonesia has not been regulated so farin an integrated manner in a separate law. The urgency of data privacy regulation in aseparate law is very important considering the number of personal data misused not inaccordance with its initial purpose such as the transaction of personal datacommercially. The regulation of data privacy is currently still regulated separately inseveral laws that do not specifically regulate the protection of personal data. TheImplementation of personal data protection needs to look at the regulations that havebeen made in other countries to then be examined and studied in accordance with thecontext of the sociological situation in Indonesia. This research discusses the generalconcept of personal data protection and compares the personal data protectionregulations in other countries and provides an analysis of the results of thesecomparisons for later application in Indonesia.